Gamification of Electronic Negotiation Training: Effects on Motivation, Behaviour and Learning - Andreas Schmid; Mareike Schoop (Group Decision and Negotiation, 2022)
Organisations are involved in various types of negotiation. As digitalisation advances, such business negotiations are to a large extent electronic negotiations. Consequently, dedicated training for such electronic negotiations is important for mastering negotiation skills. We designed a gamified negotiation system used in e-negotiation training to increase participants' motivation, engagement, use of the system's negotiation support features and to improve their decision making. The quantitative evaluation using students as subjects shows higher motivation, engagement and better system and decision-making skills for participants in the gamified training compared to a conventional training. Furthermore, female participants show higher engagement in the gamified training than males. An analysis of the individual elements in the system provides insights into participants' perceptions and shows that the inclusion of a domain-specific feedback element yields motivational results that are almost similar compared to those using traditional game elements. Organisations can employ the designed artefact for fundamental and effective e-negotiation training.
Keywords: 650; Electronic negotiation training; Negotiation support system; Gamification; Game elements; Motivation; Experiential learning